Effectiveness of high cardiorespiratory fitness in cardiometabolic protection in prediabetic rats - Chanisa Thonusin; Patcharapong Pantiya; Natticha Sumneang; Titikorn Chunchai; Wichwara Nawara; Busarin Arunsak; Natthaphat Siri-Angkul; Sirawit Sriwichaiin; Siriporn C. Chattipakorn; Nipon Chattipakorn (BMC, 2022)
Abstract Background Caloric restriction and exercise are lifestyle interventions that effectively attenuate cardiometabolic impairment. However, cardioprotective effects of long-term lifestyle interventions and short-term lifestyle interventions followed by weight maintenance in prediabetes have never been compared. High cardiorespiratory fitness (CRF) has been shown to provide protection against prediabetes and cardiovascular diseases, however, the interactions between CRF, prediabetes, caloric restriction, and exercise on cardiometabolic health has never been investigated. Methods Seven-week-old male Wistar rats were fed with either a normal diet (ND; n = 6) or a high-fat diet (HFD; n = 30) to induce prediabetes for 12 weeks. Baseline CRF and cardiometabolic parameters were determined at this timepoint. The ND-fed rats were fed continuously with a ND for 16 more weeks. The HFD-fed rats were divided into 5 groups (n = 6/group) to receive one of the following: (1) a HFD without any intervention for 16 weeks, (2) 40% caloric restriction for 6 weeks followed by an ad libitum ND for 10 weeks, (3) 40% caloric restriction for 16 weeks, (4) a HFD plus an exercise training program for 6 weeks followed by a ND without exercise for 10 weeks, or (5) a HFD plus an exercise training program for 16 weeks. At the end of the interventions, CRF and cardiometabolic parameters were re-assessed. Then, all rats were euthanized and heart tissues were collected. Results Either short-term caloric restriction or exercise followed by weight maintenance ameliorated cardiometabolic impairment in prediabetes, as indicated by increased insulin sensitivity, improved blood lipid profile, improved mitochondrial function and oxidative phosphorylation, reduced oxidative stress and inflammation, and improved cardiac function. However, these benefits were not as effective as those of either long-term caloric restriction or exercise. Interestingly, high-level baseline CRF was correlated with favorable cardiac and metabolic profiles at follow-up in prediabetic rats, both with and without lifestyle interventions. Conclusions Short-term lifestyle modification followed by weight maintenance improves cardiometabolic health in prediabetes. High CRF exerted protection against cardiometabolic impairment in prediabetes, both with and without lifestyle modification. These findings suggest that targeting the enhancement of CRF may contribute to the more effective treatment of prediabetes-induced cardiometabolic impairment.